Racing patterns of elite and non-elite male Two Oceans marathon runners - Kruger, Viljee (Department of Health and Rehabilitation Sciences, 2025)
Introduction: Limited information exists about the pacing patterns of elite and non-elite runners competing in the 56km Two Oceans Marathon. Objective: The main aim of the study was to establish and compare similarities and differences in pacing patterns between elite and non-elite male runners in the Two Oceans Marathon. Methods: Data was analysed from the Two Oceans Marathon database of finishers. Male participants across 10 races from 2007 – 2019 formed the sample group (N=25 315). The sample group was ordered fastest to slowest and subsequently divided into 8 groups (A-H) by merit of finishing times. Four timing segments (1-4) were recorded and used to calculate pace (in km/h) in each segment and mean race pace of each finisher. A Generalised Linear Mixed Effects Model (GLMM) analysis was used to examine the patterns of average pace change between groups. Results: A reduction in average pace was observed across all groups for the first three segments, with an increase in average pace for the final segment (p<0.0001). Pairwise comparison of change in pace between mean race pace across all four segments demonstrated that elite runners start the race more conservatively when compared to non- elite runners (p<0.0001). Conclusion: The findings demonstrated a parabolic type pacing pattern where elite runners demonstrated less pace variation, while non-elite runners displayed more pace variation. Non- elite runners completed the first half of the race substantially faster relative to their overall race pace. Results suggest that to achieve an optimal pacing pattern, non-elite runners should consider adopting a more realistic starting pace.